Religion and the Local Tradition of Life Cycle Rituals in Kampung Naga, West Java - Abdurrahman Misno Bambang Prawiro (Al-Albab, 2015)
West Java is one of the provinces in Indonesia which is culturally rich and diverse. The cultural wealth in Tatar Sunda (West Java) is centered on several areas that serve as the settlement of indigenous communities, from the eastern region of Ciamis, to Sukabumi. Each region has its own cultural uniqueness. Among the cultural heritage which is still in existence and preserved is Kampung Naga. It was a traditional village that firmly preserves its ancestral tradition (karuhun) passed down from generation to generation. One of the interesting features of the community of Kampung Naga is the life cycle ritual which they perform with no outside influence. This article will describe the life cycle ritual performed by the indigenous community of Kampung Naga. The ethnographic method approach is used in this study, where the author was directly involved in the process of performing the ritual. Observations, in-depth interviews and participation in any activity were used to collect verifiable data. This research showed that the daur hidup (life cycle) ritual performed by the traditional community of Kampung Naga included the rituals for pregnant mother, child birth, circumcision, gusaran, marriage, and prayer to the dead. The ritual carried out by the community is derived from the old Sundanese belief combined with Islamic culture that came in later